Free fat transplantation in the face - Drommer, Rainer B.; Mende, Ulrich (Journal of cranio-maxillofacial surgery, 1995)
Several operative procedures have been described for correction of soft tissue defects in the face. Free fat transplantation has been criticised many times. In a twelve-year period, we have carried out 19 free fat transfers from the gluteal fold, of a size ranging from the palm of a child's hand to the size of an adult hand. Follow-up has been possible in 12 patients with 14 such transfers. Initially, grafts tended to be too large and subsequent fat reduction was required. It is apparent that the tendency to resorption of non-vascularised fat can only be estimated to a limited extent. Ultrasound examination in the course of long-term follow-up showed structural changes within the grafts but none was particularly striking. The fat has a good consistency on palpation particularly for the cheeks and remains in situ after healing. This technique still has a role in suitable cases.